The functional ALDH2 polymorphism is associated with breast cancer risk: A pooled analysis from the Breast Cancer Association Consortium. Issue 6 (7th May 2019) - Ugai, Tomotaka; Milne, Roger L.; Ito, Hidemi; Aronson, Kristan J.; Bolla, Manjeet K.; Chan, Tsun; Chan, Ching W.; Choi, Ji‐Yeob; Conroy, Don M.; Dennis, Joe; Dunning, Alison M.; Easton, Douglas F.; et al.
Abstract: Background: Epidemiological studies consistently indicate that alcohol consumption is an independent risk factor for female breast cancer (BC). Although the aldehyde dehydrogenase 2 ( ALDH2 ) polymorphism (rs671: Glu>Lys) has a strong effect on acetaldehyde metabolism, the association of rs671 with BC risk and its interaction with alcohol intake have not been fully elucidated. We conducted a pooled analysis of 14 case‐control studies, with individual data on Asian ancestry women participating in the Breast Cancer Association Consortium. Methods: We included 12, 595 invasive BC cases and 12, 884 controls for the analysis of rs671 and BC risk, and 2, 849 invasive BC cases and 3, 680 controls for the analysis of the gene‐environment interaction between rs671 and alcohol intake for BC risk. The pooled odds ratios (OR) with 95% confidence intervals (CI) associated with rs671 and its interaction with alcohol intake for BC risk were estimated using logistic regression models. Results: The Lys/Lys genotype of rs671 was associated with increased BC risk (OR = 1.16, 95% CI 1.03–1.30, p = 0.014). According to tumor characteristics, the Lys/Lys genotype was associated with estrogen receptor (ER)‐positive BC (OR = 1.19, 95% CI 1.05–1.36, p = 0.008), progesterone receptor (PR)‐positive BC (OR = 1.19, 95% CI 1.03–1.36, p = 0.015), and human epidermal growth factor receptor 2 (HER2)‐negative BC (OR = 1.25, 95% CI 1.05–1.48, p = 0.012). No evidence of a gene‐environment interaction was observed between rs671 and alcohol intake ( p = 0.537). Conclusion: This study suggests that the Lys/Lys genotype confers susceptibility to BC risk among women of Asian ancestry, particularly for ER‐positive, PR‐positive, and HER2‐negative tumor types. Abstract : A novel finding of our study is the association between the Lys/Lys genotype of rs671 and estrogen receptor‐positive, progesterone receptor‐positive, and human epidermal growth factor receptor 2‐negative breast cancer. This finding infers the Lys/Lys genotype confers susceptibility to this tumor type among Asian women. In addition, no evidence of a gene‐environment interaction was observed between rs671 and alcohol intake, suggesting that acetaldehyde may be less influential in breast carcinogenesis.